Orthopaedic Group Practice Size Is Increasing - Jordan R. Pollock, B.S; M. Lane Moore, B.S; Jacob S. Hogan, B.S; Jack M. Haglin, M.D., M.S; Joseph C. Brinkman, M.D; Matthew K. Doan, B.S; Anikar Chhabra, M.D (Elsevier, 2021)
Purpose: To analyze recent trends in orthopaedic surgery consolidation and quantify these changes temporally and geographically from 2012 to 2020. Methods: We performed a retrospective cross-sectional analysis of orthopaedic surgeon practice size in the United States using 2012 and 2020 data obtained from the Physician Compare database. Results: Although we observed an increase from 21,216 unique orthopaedic surgeons in 2012 to 21,553 in 2020 (1.6% increase), the number of practices experienced a large decrease from 7,299 practices in 2012 to 5,829 in 2020 (20.1% decrease). The proportion of orthopaedic surgeons working in solo practices decreased from 13.2% (2,790) in 2012 to 7.4% (1,595) in 2020, and the proportion of orthopaedic surgeons working in groups sized 2 to 24 decreased from 35.3% (7,482) in 2012 to 22.2% (4,775) in 2020. In contrast, groups sized 25 to 99 have grown from 20.7% (4,387) of all orthopaedic surgeons to 23.4% (5,048) in 2020. Groups sized 100 to 499 have increased from 16.9% (3,593) in 2012 to 24.1% (5,190) in 2020, whereas groups sized 500 or greater have grown from 14% (2,964) in 2012 to 22.9% (4,945) in 2020. The number of unique group practices showed a significant decrease in the number of solo groups, which comprised 43.8% (3,200) of the total number of individual practices in 2012, decreasing to 32% (1,886) in 2020. All other groups increased in number and proportionally from 2012 to 2020. Conclusions: This study shows that over the period from 2012 to 2020, there has been a substantial trend of orthopaedic surgeons shifting to increasing practice sizes, potentially indicating that more orthopaedic surgeons are working for large health care organizations rather than small independent practices. Clinical Relevance: The impact of these changes should be examined to determine large-scale effects on patient care, payment models, access, and outcomes, along with physician compensation, lifestyle, and satisfaction.